PERIODE PERKEMBANGAN KEKUASAAN KEHAKIMAN DI INDONESIA SETELAH MERDEKA (TELAAH UNDANG- UNDANG TENTANG KEKUASAAN KEHAKIMAN) - Faisal, Ahmad (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The law always changes along with the changing times. In an effort to respond to changes in the law, the judicial power should also change so that it can accommodate changes in the times and laws that occur. Since Indonesia's independence, there have been changes in laws related to judicial power. This research is library research using laws related to judicial power as the study material. From the results of the research conducted, it is known that changes in the judicial power law have occurred six times since Indonesia's independence. Currently, the judicial power has been divided into several parts, namely the Supreme Court with district courts, religious courts, state administrative courts and military courts and the Constitutional Court. In addition to these two institutions, there is also the Judicial Commission.